Engineering spin-orbit effects and Berry curvature by deposition of a monolayer of Eu on WSe2 - Carbone, Johanna P.; Go, Dongwook; Mokrousov, Yuriy; Bihlmayer, Gustav; Bluegel, Stefan (Physical Review B, 2022)
Motivated by recent progress in two-dimensional (2D) spintronics, we present a monolayer of Eu deposited on 1H-WSe2 as a promising platform for engineering spin-orbit effects and Berry curvature. By first-principles calculations based on density functional theory, we show that Eu/WSe2 exhibits intriguing properties such as high magnetic anisotropy, valley-dependent polarization of spin and orbital angular momenta, and Rashba textures. These originate from magnetic and spin-orbit proximity effects at the interface and the interplay between localized 4f magnetic moments of Eu and mobile charge carriers of Eu and WSe2. The analysis of the magnetic properties reveal a ferromagnetic configuration with an out-of-plane easy axis of the magnetization, which favor a pronounced anomalous Hall effect in the proposed system. Thus, we promote 4f rare-earth metals deposited on top of a transition-metal dichalcogenides as a promising platform for 2D spintronics.
CRIS-Team Scopus Importer:2023-03-27